Changes in Halal Product Guarantee Regulations Perspective of Legal Politics and Consumer Rights Protection - Evi Sopiah; Abdulah Safe'i; Elly Marlina; Heris Suhendar (Khazanah Hukum, 2024)
A halal product guarantee is a legal certainty regarding the halal status of a product produced by a business entity, which is evidenced by the issuance of a halal certificate by the government. The focus of the research examines the changes in halal product guarantee regulations within the Omnibus Law using a legal politics and consumer legal protection approach. This research is normative legal research whose object of study is the history of changes to halal product guarantee regulations in the Job Creation Act and its implications for consumer legal protection. Legal and non-legal materials were obtained from document studies and literature studies in the form of academic texts, draft laws, problem inventory lists, laws and regulations related to halal product guarantees and consumer protection, journals, and other documents relevant to the research issue. Changes in halal product guarantee regulations are a strategic step to strengthen the national halal industry and increase the competitiveness of Indonesian halal products in the global market. Changes in regulations prioritizing business actors' statements as the basis for halal certification can overcome the low awareness of business actors regarding halal certification obligations. In addition, changes to halal product guarantee regulations provide legal protection for consumers through guarantees of legal certainty, both preventively and repressively through self-declaration policies by implementing special limitations, conditions, and criteria for halal certification obligations for micro and small businesses, as well as administrative sanctions. and criminal penalties for business actors who commit acts or violations that can harm consumers.